Functional photoacoustic calcium imaging using chlorophosphonazo III in a 3D tumor cell culture - Liu, Wei-Wen (Biomed Opt Express, 2021)
This study demonstrates that chlorophosphonazo III (CPZ III) can be used as a contrast agent for photoacoustic calcium imaging. CPZ III can pass across the plasma membrane for labeling intracellular Ca(2+) without cytotoxicity. In optical-resolution photoacoustic microscopy (OR-PAM), the photoacoustic (PA) signal intensity was strongly correlated with the presence of CPZ III and Ca(2+) at various concentrations. The sensitivity of PA signal reception was enhanced by using an 8 MHz single-element focused ultrasound detector due to their matched frequency characteristics. Differences in the PA signal intensity were successfully found between the core and margin areas of tumorspheres in three-dimensional cell cultures. These findings indicate that CPZ III can serve as a novel PA contrast agent for functional Ca(2+) imaging using OR-PAM.